Structural Evolution and Properties of Praseodymium Antimony Oxochlorides Based on a Chain-like Tertiary Building Unit - Wen, Wei-Yang; Hu, Bing; Pan, Tian-Yu; Li, Zi-Wei; Hu, Qian-Qian; Huang, Xiao-Ying (Molecules (Basel, Switzerland), 2023)
Unveiling the structural evolution of single-crystalline compounds based on certain building units may help greatly in guiding the design of complex structures. Herein, a series of praseodymium antimony oxohalide crystals have been isolated under solvothermal conditions via adjusting the solvents used, that is, [HN(CH2CH3)3][FeII(2,2′-bpy)3][Pr4Sb12O18Cl15]·EtOH (1) (2,2′-bpy = 2,2′-bipyridine), [HN(CH2CH3)3][FeII(2,2′-bpy)3]2[Pr4Sb12O18Cl14)2Cl]·N(CH2CH3)3·2H2O (2), and (H3O)[Pr4Sb12O18Cl12.5(TEOA)0.5]·2.5EtOH (3) (TEOA = mono-deprotonated triethanolamine anion). Single-crystal X-ray diffraction analysis revealed that all the three structures feature an anionic zig-zag chain of [Pr4Sb12O18Cl15−x]n as the tertiary building unit (TBU), which is formed by interconnections of praseodymium antimony oxochloride clusters (denoted as Pr4Sb12) as secondary building units. Interestingly, different arrangements or linkages of chain-like TBUs result in one-dimensional, two-dimensional layered, and three-dimensional structures of 1, 2, and 3, respectively, thus demonstrating clearly the structural evolution of metal oxohalide crystals. The title compounds have been characterized by elemental analysis, powder X-ray diffraction, thermogravimetric analysis, and UV-Vis spectroscopy, and the photodegradation for methyl blue in an aqueous solution of compound 1 has been preliminarily studied. This work offers a way to deeply understand the assembly process of intricate lanthanide-antimony(III) oxohalide structures at the atomic level.